THE EFFECT OF JOB INSECURITY ON COMPULSORY CITIZENSHIP BEHAVIOR: THE MEDIATING ROLE OF EMOTIONAL EXHAUSTION AMONG AIRPORT OUTSOURCING EMPLOYEES - Sangaji Eko Sambodho (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Outsourcing employees in airport operational environments frequently face unstable employment conditions, short-term contracts, and limited job security, which may increase psychological strain and shape work behaviors beyond formal job requirements. Understanding the mechanism linking job insecurity to compulsory citizenship behavior (CCB) is therefore important in vulnerable employment settings. This study aims to examine the effect of job insecurity on CCB and investigate the mediating role of emotional exhaustion among airport outsourcing employees in Indonesia. A quantitative cross-sectional survey was conducted involving 609 outsourced employees working at four major Indonesian airports. Respondents were selected using purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that job insecurity had a positive and significant effect on emotional exhaustion (β = 0.331, p < 0.001), while emotional exhaustion positively affected CCB (β = 0.646, p < 0.001). Furthermore, emotional exhaustion significantly mediated the relationship between job insecurity and CCB through a complementary partial mediation mechanism. The findings indicate that job insecurity functions as a structural job demand that depletes employees’ emotional resources and increases the likelihood of engaging in compulsory rather than voluntary extra-role behaviors.